A highly temperature-stable and complete-resonance rotary giant magnetostrictive ultrasonic system. (15th January 2022) - Ma, Ke; Wang, JianJian; Zhang, Jianfu; Feng, Pingfa; Yu, Dingwen; Ahmad, Shahzad
Highlights: A temperature-stable and complete-resonance separated rotary giant magnetostrictive ultrasonic (SRGU) system is presented. The mechanical and energy transmission structures of the SRGU are simplified by removing the fixed and rotary magnetic cores, with the design methods of them. SRGU maintains complete resonance during work, thus obtains stable vibration and small heat. SRGU works continuously and stably for 9 h at 10 μm amplitude without cooling system. Abstract: Rotary ultrasonic machining is regarded as a superior machining method for hard and brittle materials. It utilizes ultrasonic tool vibration to improve the material machinability, resulting in reduced cutting force and improved machining efficiency. The temperature stability and resonance quality of the ultrasonic system are critical for the reliable generation of ultrasonic vibration. This study presents a temperature-stable and complete-resonance separated rotary giant magnetostrictive ultrasonic (SRGU) system with novelly designed mechanical structures to improve energy transmission and heat dissipation. A theoretical analysis was performed to demonstrate the design principle of the SRGU system. By abolishing the contactless power system of fixed and rotary parts used in the conventional rotary ultrasonic system, and by using a unique incomplete shell, design methods of the mechanical structure, magnetic circuit, and excitation coil of the SRGU system were proposed. A prototype of the SRGU system was then fabricated and tested to verify the feasibility and efficacy of the proposed design methods. The experimental results demonstrated that the SRGU worked well with much-improved ultrasonic vibration stability and better complete resonance as compared to the conventional ultrasonic system. It was found to work with an ultrasonic amplitude of 10 μm for a continual 9 h with a temperature increase of only 3 °C. Graphical abstract: Image, graphical abstract